THE ROLE AND IMPORTANCE OF FORMAL ELEMENTARY EDUCATION FOR THE DEVELOPMENT OF ENTREPRENEURIAL ABILITIES IN ACCORDANCE WITH THE ETHICAL PRINCIPLE - Manić, Aleksandra; Trajković, Svetlana P (Journal of process management and new technologies, 2019)
Education means an organized activity of transferring and acquiring knowledge, with the development of certain abilities and skills, and the formation of working and living attitudes. Historically, this activity is as old as humanity, evolving in parallel, with socio-economic development, in order to grow into a particularly important activity, important for every social community. Investing in people's education appears as an important driving resource, forms the basis of society's development and is part of the development strategy of all developed countries. The most important form of entrepreneurship manifestation is through the economic context, where the measure of success, the readiness of entrepreneurs to rapid changes, caused by modern business conditions, for which the most important is pre-school education. Entrepreneurship and entrepreneurial education have never been more important, especially if the number of unemployed younger age groups is taken into account. The overall effectiveness of entrepreneurship, whether self-employed or group entrepreneurship, requires, besides general conditions and psychic characteristics of entrepreneurs, a significant level of entrepreneurial education, so education for entrepreneurship must be taken as a very important component in the development of entrepreneurship. Entrepreneurial education should be treated as a production investment, and not as consumption, because the education of accumulation of capital, and for this reason, should begin with education at an earlier age, through formal education. Using natural resources, in order to improve their own quality of life, man has broken the natural balance and created a series of problems. It paradoxically caused counter effects, but also influenced the change of perception. Namely, the anthropocentric approach to nature must be replaced by biocentric, which makes nature and its laws closer to all human spheres. This requires a special approach to entrepreneurship, in accordance with the principles close to nature, in the earliest period of life through formal primary education.